Plasma and Red Cell Reference Intervals of 5-Methyltetrahydrofolate of Healthy Adults in Whom Biochemical Functional Deficiencies of Folate and Vitamin B12 Had Been Excluded - Agata Sobczyńska-Malefora; Dominic J. Harrington; Kieran Voong; Martin J. Shearer (Advances in Hematology)
5-Methyltetrahydrofolate (5-MTHF) is the predominant form of folate and a strong determinant of homocysteine concentrations. There is evidence that suboptimal 5-MTHF availability is a risk factor for cardiovascular disease independent of homocysteine. The analysis of folates remains challenging and is almost exclusively limited to the reporting of “total” folate rather than individual molecular forms. The purpose of this study was to establish the reference intervals of 5-MTHF in plasma and red cells of healthy adults who had been prescreened to exclude biochemical evidence of functional deficiency of folate and/or vitamin B12. Functional folate and vitamin B12 status was assessed by respective plasma measurements of homocysteine and methylmalonic acid in 144 healthy volunteers, aged 19–64 years. After the exclusion of 10 individuals, values for 134 subjects were used to establish the upper reference limits for homocysteine (13 μmol/L females and 15 μmol/L males) and methylmalonic acid (430 nmol/L). Subjects with values below these cutoffs were designated as folate and vitamin B12 replete and their plasma and red cell 5-MTHF reference intervals determined, N=126: 6.6–39.9 nmol/L and 223–1041 nmol/L, respectively. The application of these intervals will assist in the evaluation of folate status and facilitate studies to evaluate the relationship of 5-MTHF to disease.